APROVECHAMIENTO DEL SUERO DE LECHE COMO BEBIDA ENERGIZANTE PARA MINIMIZAR EL IMPACTO AMBIENTAL - Hannibal, Brito; Antonio, Santillán; Mercy, Arteaga; Evelyn, Ramos; Paola, Villalón; Adriana, Rincon (European Scientific Journal, ESJ, 2015)
The whey or whey is the fluid that separates cheese during collection and contains components that are not integrated into the coagulation of casein. It has high nutritional content, however, a small percentage is used as feed for farm animals and the remainder discarded, causing pollution problems in rivers and soils. Protein and lactose become pollutants when the whey is thrown into the atmosphere, because the load of organic matter it contains, it allows the reproduction of microorganisms to produce significant changes in the biochemical oxygen demand of the water, and the amount of lactic acid, significantly altered biological processes. Therefore, the possibility of using high amount of nutrients and amino acids present in the whey, through the development of an energy drink, considering the growing number of college students who use them and the environmental impact was raised produced by dairies to discard the whey. Based on experimental tests best suited for the preparation of the energy drink resulting in two formulations with different composition process was selected. Fitness drink consumption was determined through physical, chemical and microbiological analyzes based on the rule of Ecuadorian Standards Institute (INEN): 2609 (2012), whey drinks. Through surveys of college students consumption of energy and the best organoleptic characteristics it is determined formulating getting greater acceptability.